Alexander Graham Bell - Kramer, Barbara (Washington, D.C. : National Geographic, 2015)
Presents the life and career of Alexander Graham Bell, examining how he invented the telephone and his work with the deaf.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record.
Keywords: Bell, Alexander Graham, -- 1847-1922 -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature; Telephone -- History -- Juvenile literature; Bell, Alexander Graham, -- 1847-1922.; Inventors; Telephone -- History; Bell, Alexander Graham, -- 1847-1922.; Inventors; Telephone; United States; Electronic books- OSLIS; Biography; History; Juvenile works; Electronic books